2017
DOI: 10.7600/jpfsm.6.111
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sustained high-intensity exercise on executive function

Abstract: Exercise-induced changes in executive function affect the control of action in a dynamic environment. This study aimed to examine the effect of sustained high-intensity exercise on executive function. Nine healthy male and female participants (age, 21-28 years) completed an exercise session with 65-min treadmill running at 75% V ・ O 2 max. Executive function was assessed before and after exercise with the Stroop Color and Word Test that included congruent and incongruent conditions. The reaction time and respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Not surprisingly, athletes with slower baseline cognitive processing speeds (e.g., longer reaction times) demonstrate mechanics that may result in greater ACL loading during execution of unplanned landing and cutting maneuvers [ 67 69 ]. Fatigue induced by intense exercise may result in decrements in cognitive processing (indicative of a ‘supraspinal’ effect) [ 70 76 ]. In addition, specific cognitive functions, such as concentration, deteriorate when experiencing higher stress levels, decreasing an individual’s ability to perform well in tasks that require high levels of attentional control (being ‘in the game’) [ 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…Not surprisingly, athletes with slower baseline cognitive processing speeds (e.g., longer reaction times) demonstrate mechanics that may result in greater ACL loading during execution of unplanned landing and cutting maneuvers [ 67 69 ]. Fatigue induced by intense exercise may result in decrements in cognitive processing (indicative of a ‘supraspinal’ effect) [ 70 76 ]. In addition, specific cognitive functions, such as concentration, deteriorate when experiencing higher stress levels, decreasing an individual’s ability to perform well in tasks that require high levels of attentional control (being ‘in the game’) [ 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported soccer officials attain 86% accuracy in decision-making during competition (Mallo, Frutos, Juarez, & Navarro, 2012), whereas Australian football umpires reported 84% accuracy when awarding free kicks during competition (Elsworthy, Burke, Scott, Stevens, & Dascombe, 2014). Regardless of this need for high-quality officiating and decision-making, recent studies have focused on the physical and cognitive factors underpinning decision-making processes in athletes across sports (Almonroeder, Tighe, Miller, & Lanning, 2018;Konishi et al, 2017;Scanlan, Humphries, Tucker, & Dalbo, 2014). Because the cognitive skills of athletes and sports officials are specific to their roles, the prevailing research on athletes should not be considered completely transferable to sports officials (Williams & Davids, 1995).…”
Section: Decision-making In Sports Officialsmentioning
confidence: 99%
“…14,39,48 Almonroeder et al 3 summarized how exerciseinduced fatigue might decrease cognitive processing, indicating a ''supraspinal effect'' of physical fatigue in addition to its well-known influence at the peripheral (muscular) level. 33 Ultimately, physical fatigue seems to have the potential to produce concurrent detrimental effects on both cognitive and motor function when performing athletic movements with high temporal constraints and applied cognitive loads, as typical during sports. Therefore, the interaction between cognition and fatigue may be an important, but understudied, area for novel clinically relevant approaches to risk screening and injury prevention.…”
Section: Introductionmentioning
confidence: 99%